LANDFILL DESIGN "THE VIZCACHA PUENTE PIEDRA DISTRICT, LIMA-PERU - Erazo-Erazo, R. (2000)
This work has the goal of designing a system to treat solid municipal wastes by recycling and final disposition in a sanitary filling field. Studies of handling solid wastes in the northem part of Lima, determine a rate of treatment of 800 TM/day. The filling field will be located near the Pan American high way, around the 38,700 Km in the district of Puente Piedra, taking around 100 hectares of field. Studies on climatological, geophysical, geodinamic and social impacts, determine that the environmental impact on the ecosystem will be minimal. Finally, the useful lile of the facility is estimated in 45 year at a total final deposition cost of US$2,60 /TM.